Monitoring the efficacy of immunisation against theileriosis caused by Theileria parva - Morzaria, S.P. (International Livestock Research Institute, 1996)
Tick-borne diseases (TBDs) caused by different protozoan and rickettsial species occur all over the world but their greatest impact is in the tropics and subtropics where they cause huge losses mainly in improved breeds of cattle. The economically important tick-transmitted diseases of cattle are caused by the protozoan parasites Babesia bigemina and B. bovis, and Theileria parva and T. annulata, and by the rickettisial organisms Anaplasma marginale and Cowdria ruminantium. In the tropics, countries in the eastern and central regions of Africa are probably most affected. In these regions theileriosis, caused by T. parva, combined with babesiosis, anaplasmosis and cowdriosis, continues to restrict the introduction of improved breeds of cattle. Live vaccines for babesiosis, anaplasmosis and cowdriosis have been available and used for several years. Despite this, the intensive application of acaricides on cattle has been required mainly to control the brown ear tick, Rhipicephalus appendiculatus, the principal vector of T. parva, for which no vaccine was available. In the last 20 years, a significant research effort has been put into the development of a vaccine against T. parva. This has resulted in the infection-and-treatment method of immunisation, which has opened up the possibility of reducing the use of acaricides. The FAO Regional Programme on Control of Ticks and Tick-borne Diseases is deploying live vaccines to control TBDs (particularly theileriosis) as part of the integrated control of ticks and TBDs in the predominantly small holder dairy sector in the region. The live vaccines for tick-borne diseases other than theileriosis have been used for several decades and their efficacies have been well defined. However, the infection-and-treatment method immunisation against T. parva has only been used on a limited scale and the need to assess efficacy evaluate delivery systems and measure the long-term impact of immunisation is clearly recognised. This paper identifies the problems of producing and delivering a live vaccine against theileriosis and the parameters that need to be monitored to evaluate the efficacy and long-term biological impact of immunisation. The paper also briefly describes the technologies that are available to monitor immunisation.